Experimental studies to reduce usage of fossil fuels and improve green fuels by adopting hydrogen−ammonia−biodiesel as trinary fuel for RCCI engine - Ramachandran, Elumalai; Krishnaiah, Ravi; Perumal Venkatesan, Elumalai; Medapati, Sreenivasa Reddy; Sabarish, Rajagopalan; Khan, Sher Afghan; Asif, Mohammad; Linul, Emanoil (American Chemical Society, 2023)
This study investigates the feasibility of hydrogen addition to achieve lower emissions and higher thermal efficiency in an ammonia−biodiesel-fueled reactivity-controlled compression ignition (RCCI) engine. A single-cylinder light-duty water-cooled compression ignition (CI) engine was adapted to run in RCCI combustion with port-injected ammonia and hydrogen as low reactive fuel (LRF) and direct-injected algal biodiesel as high reactive fuel (HRF). In our earlier study, the ammonia substitution ratio (ASR) was optimized as 40%. To optimize fuel and engine settings, hydrogen is added in quantities ranging from 5 to 20% by energy share. The combustion, performance, and emission characteristics were investigated for the trinary fuel operation. The result shows that the 20% hydrogen premixing with 40% ammonia−biodiesel RCCI operation increased the peak cylinder pressure (CP), peak heat release rate (HRR), and cumulative heat release rate (CHRR) by 15.12, 25.15, and 26.68%, respectively. Ignition delay (ID) and combustion duration (CD) were decreased by 15.53 and 11.24%, respectively. The combustion phasing angle was advanced by 4 °CA. The brake thermal efficiency (BTE) was improved by 15.49%, and brake-specific energy consumption (BSEC) was reduced by 21.92%. While the nitrogen oxide (NOx) level was significantly increased by about 31.82%, the hydrocarbon (HC), carbon monoxide (CO), smoke, and exhaust gas temperature (EGT) were reduced by 24.53, 28.16, 25.82, and 17.47% as compared to the optimized ASR40% combustion.